Review dalam Pembuatan Arang Aktif Berbasis Limbah Pertanian Dengan Microwave - Fithry, Dwi Annisa; Jusnita, Jusnita; Legawati, Lisa; Ermal, Dini Aulia Sari; Prayogo, Hidayat (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Conventional handling of biomass waste, such as burning biomass, can cause other problems, and is not effective. Another common handling method is utilizing biomass waste. Second, conventional handling does not significantly reduce the amount of biomass waste. Microwave heating uses several power parameters and activation time to determine the effect of power and activation time on iodine number and surface area [25]. Activated charcoal is used as a raw material because it is hard charcoal and has good quality, and microwaves are used because it saves energy and time. Microwave treatment to study the effect of concentration and time of microwave irradiation separately on iodine number and adsorption capacity. The results of the FTIR spectra show that activated carbon has an –OH group. The results of the adsorption test showed that the activated carbon that had been prepared was able to absorb ions at the optimum concentration. Adsorption isotherm studies were carried out using the Langmuir equation. Microwave irradiation time also has a significant effect on the quality of activated carbon in the microwave irradiation time range